Efficiency of Tigecycline and other Antimicrobials to Extended Spectrum Beta Lactamase Producing Gram Negative Bacteria in Blood Culture Isolates and Detection in Activity of Carbapenemases (Annals of Medical Research, 2021)
None
Keywords: Extended Spectrum Β-Lactamase; Tigecycline; Modified Hodge Test.